2005
DOI: 10.1029/2005gl023514
|View full text |Cite
|
Sign up to set email alerts
|

Significant latitudinal gradient in the surface ozone spring maximum over East Asia

Abstract: The climatology of surface ozone over East Asia was investigated at a wide range of latitudes by integrating continuous measurements from Japanese monitoring networks. Although a spring maximum and a summer minimum were observed at all seven remote stations, significant latitudinal differences in the seasonal cycles were found, particularly in spring. At low latitudes (20–30°N) the spring maximum appears in March, while it appears in April at high latitudes (40–50°N), and in May at middle latitudes (30–40°N). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
77
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 107 publications
(87 citation statements)
references
References 17 publications
10
77
0
Order By: Relevance
“…Our previous application and evaluation of CMAQ are found elsewhere [Tanimoto et al, 2005;Uno et al, 2007]. The horizontal and vertical resolutions are 80 Â 80 km 2 and 14 layers up to 23 km, respectively.…”
Section: Regional Ctm and Emissions Inventorymentioning
confidence: 99%
“…Our previous application and evaluation of CMAQ are found elsewhere [Tanimoto et al, 2005;Uno et al, 2007]. The horizontal and vertical resolutions are 80 Â 80 km 2 and 14 layers up to 23 km, respectively.…”
Section: Regional Ctm and Emissions Inventorymentioning
confidence: 99%
“…In Japan, it has been reported that various substances, including non-sea-salt sulfate (nss-SO 4 2-), heavy metals and organic compounds, are transported from the Asian continent to Japan during winter and spring when the airflows from the Asian continent are dominant (Mukai et al, 1990(Mukai et al, , 1994Ichikawa et al, 1998;Tanaka and Sakata, 2002;Sakata and Marumoto, 2005;Sakata et al, 2006). Moreover, Tanimoto et al (2005) showed that the spring maximum of surface O 3 over Japan is significantly caused by NO x from sources in China and Korea. On the other hand, Jaffe et al (2005) and Weiss-Penzias et al (2006) observed the export of CO, O 3 , Hg 0 and particles from Asian long-range transport (ALRT) during spring at the Mt.…”
Section: Introductionmentioning
confidence: 99%
“…Yamaji et al (2006) used a regional-scale atmospheric chemistry transport model and showed that about 10-20 ppb of ozone (about 20-30% of the total) was attributable to regional production in April-May over western Japan. Naja and Akimoto (2004) and Tanimoto et al (2005Tanimoto et al ( , 2009) investigated the overall influence of the expanding Asian economy on ozone levels over Japan. They all looked at the entire regional production of ozone without discriminating between (1) and (2).…”
Section: Introductionmentioning
confidence: 99%